INCIDENCE OF ACUTE KIDNEY INJURY IN PATIENTS OF ACUTE GASTROENTERITIS ADMITTED AT LADY READING HOSPITAL, PESHAWAR - HAYAT , FS; IKHTIAR , Z; BADSHAH , I; HUSSAIN , M; HADI , M; KHAN , I; IKHTIAR , H; KHAN , A (Biological and Clinical Sciences Research Journal, 2023)
Acute gastroenteritis affects all age groups alike, is a common cause of hospitalization worldwide, and is the most common known cause of preventable acute kidney injury. AKI may be defined as a sudden decrease in kidney function, which results in reduced filtration capability of the kidneys, accumulation of waste products, and their resultant clinical manifestations. The level of insult may range from mild to severe, requiring simple oral rehydration most times, while in a few cases needing intervention in the form of hemodialysis. The elderly population is more prone to develop AKI due to age-related deterioration in renal function. An overall positive outcome has been associated with early hemodialysis in progressively deteriorating AKI and critically ill patients. A prospective observational study was conducted on 40 patients with AKI secondary to acute gastroenteritis admitted to MTI, Lady Reading Hospital, Peshawar, KP, Pakistan, from February 2023 to June 2023. These patients were selected from 142 patients with acute gastroenteritis admitted to MTI, Lady Reading Hospital, Peshawar. Data collected was analyzed using SPSS 20. This study was conducted on 40 patients with a mean age of 39.82±16.54 years. Gender: Our study included 22 (55%) male and 18 (45%) female patients. We observed that 11 (27.5%) patients on dialysis had developed AKI secondary to AGE. We observed that older patients above 40 years of age who developed AKI secondary to AGE had a significantly higher frequency of hemodialysis (47.1%) as compared to patients less than 40 years of age (13%) (P = 0.01). According to the comparison of mortality with age groups, no mortality was seen in the age group of < = 40 years; however, there were 2 mortalities in the age group of > 40 years. One patient expired after 2 sessions, and one expired after 5 sessions and a prolonged stay. Our results showed a significant association between favorable outcomes and dialysis sessions for the less than 40 age group (P = 0.0001) and the more than 40 age group (P = 0.004). Although the overall outcome with dialysis was favorable, with good recovery, the age group of 40 years and above showed significantly higher rates of hemodialysis requirement and more morbidity and mortality compared to the age group of 40 years and less. 40(28.2%) patients with Acute gastroenteritis developed Acute kidney injury. Among these patients, 11 (27.5%) required hemodialysis. This concluded that 29 patients (72.5%) were treated conservatively and discharged with full recovery of renal function. 72.7% requiring hemodialysis were above 40 years of age, proving that the incidence of AKI and its severity increased.